New product success evaluation : a case study of Starbucks Singapore. - Huang, Oswald Tak Wan. (2008)
The objective of this applied research project is to apply, evaluate and draw conclusion from these identified critical success factors in a service industry scenario. For the purpose of this research paper, Starbucks Singapore was selected as a case study. Based on these factors, we determined whether Starbucks is successful and explored if there is expectation gap between what consumers expect and what the management of Starbucks delivers.